A novel approach to design of a power factor correction and total harmonic distortion reduction-based BLDC motor drive - Bin, Li; Abdeen, Zain ul; Abrar, Muhammad; Abdul Muqeet, Hafiz; Shahzad, Muhammad; Zulfiqar, Muhammad; Hussain, Muhammad Majid (Frontiers in Energy Research, 2023)
This study describes a Novel Approach of Power Factor Correction and Total Harmonic Distortion Reduction based BLDC motor drive for Energy Management System. The drive is designed to obtain a reduced total harmonic distortion for power factor correction. The basic design of the BLDC motor drive contains ac voltage source as input source for a diode bridge rectifier. The output dc voltage is filtered out to reduce ripples. The smooth dc output voltage is supplied to the modified zeta converter. The output voltage of the modified zeta converter is controlled by using pulse width modulation (PWM). The modified zeta converter is utilized in discontinuous inductor current mode (DICM) for better power factor. This controlled dc voltage is supplied to voltage source inverter as input. Voltage source inverter (VSI) is designed to convert input dc into suitable ac voltage source. The output voltage of VSI depends upon switching patterns applied to power transistors generated by SVPWM. Actually, the output of VSI is supplied to BLDC Motor for speed control. The proposal is to simulate and assess for improved power factor, low total harmonic distortion, and better speed control via MATLAB/Simulink environment in sim power system and sim scape toolbox.